2018
DOI: 10.1111/clr.13340
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival rates and biologic complications with implant‐supported fixed complete dental prostheses: A retrospective study with up to 12‐year follow‐up

Abstract: Purpose To report the rate of technical complications and prosthesis survival in a cohort of edentulous patients treated with implant‐supported fixed complete dental prostheses (IFCDPs) after a mean observation period of at least 1 year. Materials and Methods The single‐visit examination included clinical and radiographic assessment, occlusal analysis, photographs and questionnaire assessing patient satisfaction in a cohort of 52 patients rehabilitated with 71 IFCDPs (supported by 457 implants). The IFCDPs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 28 publications
5
94
1
7
Order By: Relevance
“…We can observe that the results were lower than those observed in the present study and the difference could be due to the surface characteristics of the implants used, and this observation was corroborated by scientific evidence (De Bruyn et al, ). Another retrospective study on 457 moderately rough dental implants supporting 71 FAISRs placed in 52 patients explored the cumulative survival rate over a period of 12 years from loading (Papaspyridakos et al, ). The authors reported a CSR% of 95.93% after 9 years and 83.14% after 10 years reporting that one third of the total failures (2 out of 6) occurred between 9 and 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We can observe that the results were lower than those observed in the present study and the difference could be due to the surface characteristics of the implants used, and this observation was corroborated by scientific evidence (De Bruyn et al, ). Another retrospective study on 457 moderately rough dental implants supporting 71 FAISRs placed in 52 patients explored the cumulative survival rate over a period of 12 years from loading (Papaspyridakos et al, ). The authors reported a CSR% of 95.93% after 9 years and 83.14% after 10 years reporting that one third of the total failures (2 out of 6) occurred between 9 and 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…One recently published consensus statement suggested to make a diagnosis of peri‐implantitis in presence of bleeding and/or suppuration on gentle probing, in presence of increased probing depth as compared to previous examinations and when evaluating the presence of bone loss beyond crestal bone changes resulting from initial bone remodeling (Berglundh et al, ). In the present study, we considered the presence of peri‐implantitis when we detected evidence of bleeding/suppuration (evidence of inflammatory reaction) and a concomitant bone resorption process of 2 mm or more, as it was done in other similar studies (Heitz‐Mayfield et al, ; Papaspyridakos et al, ). The present study reported the data about peri‐implantitis both implant‐based and patient‐based following the recommendation of the paper published by Sanz, Chapple, and Working Group 4 of the ().…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations